A BIBLIOMETRIC PERSPECTIVE ON STUDENT MOTIVATION AND INTEREST IN MATHEMATICS - Mohd Zaki, Nurul Izzati; Mustapa, Shazana; Ahmad, Sariah (INTERNATIONAL JOURNAL OF MODERN EDUCATION (IJMOE), 2025)
This study presents a bibliometric perspective on student motivation and interest in mathematics, aiming to map the intellectual structure, research trends, and collaborative networks in this domain. Motivation and interest have long been recognized as crucial factors in shaping students’ mathematical learning outcomes. Yet, the fragmented nature of the literature often limits a comprehensive understanding of their development. To address this gap, bibliometric techniques were employed using a dataset of 993 publications retrieved from Scopus through an advanced search with the keywords “mathematics,” “student,” and “motivation.” The analysis followed a systematic approach: first, data collection from Scopus ensured coverage of peer-reviewed studies across multiple disciplines; second, Scopus Analyzer was applied to generate statistical insights and graphical representations of publication trends, citation patterns, and authorship distribution; third, OpenRefine was used to clean, refine, and harmonize inconsistencies in the dataset; and finally, VOSviewer software facilitated the visualization of keyword co-occurrence, co-authorship by country, and thematic clustering. The results revealed that research productivity has shown steady growth, with notable peaks in the last five years, reflecting increasing attention to motivational factors in mathematics education. The most cited contributions were strongly connected to active learning, student engagement, and the integration of digital technologies in mathematics learning. Furthermore, co-occurrence analysis identified six major clusters, representing themes such as learning systems, problem-solving approaches, mathematics anxiety, technology-enhanced learning, and psychological constructs like self-efficacy and metacognition. Collaboration networks showed that the United States, China, and Indonesia emerged as leading contributors, with diverse international partnerships shaping the global research landscape. This study contributes to the body of knowledge by providing an evidence-based overview of research dynamics in student motivation and interest in mathematics, offering valuable insights for educators, researchers, and policymakers to strengthen student-centred learning and foster innovation in mathematics education.